From Theory to Practice: The Effects of Community of Practice Implementation on Out-of-School Youth in the Philippines - Pantaleon, Alfred; Bautista, Chester Allan F.; Villanueva, ZJ G.; Gundran, Tricia L.; Fabro, Arrianne Michelle F. (Fakultas Tarbiyah dan Ilmu Keguruan IAIN Palu, 2024)
Communities of Practice (CoP) aims to provide services and skills to partner communities while also establishing links to communicate learned knowledge to broader groups of people. This study identified and analyzed the impact of communities of practice in Barangay Nagtenga, Sta. Cruz, Ilocos Sur. It used a mixed quantitative and qualitative study approach to evaluate the level of satisfaction of the 18 CoP participants as well as their CoP learning and experience. The data demonstrated high levels of CoP satisfaction, notably with resource speakers and the quality of service provided. Participants shared their learning experiences during the CoP, focusing on themes such as knowledge acquisition, skill development, learning transfer to practice, and entrepreneurial management. This study emphasizes the importance of CoPs in empowering marginalized groups and promoting personal and professional development. Recommendations include maintaining and growing CoP initiatives, as well as conducting frequent evaluations to ensure continuous improvement.